Analiza pracy i opłacalności budowy przydomowych instalacji do oczyszczania ścieków - Wańska, Anna (My University, 2011)
Water is an essential ingredient for life. Because its belongs to exhausted resources it must be used in a rational way. Sewage - polluted, pathogenic and unable for human use water is a big problem. Removing contamination by using mechanical, physico - chemical and biological methods is a solution of the problem. In places where there is no sanitary sewer systems, commonly solutions are septic tanks or household sewage treatment plants. The main subject of work is the project of household sewage treatment plant for a detached house. Work of septic drain fields is more economical and ecological effective.

Woda jest składnikiem niezbędnym do życia. Jej wyczerpywalne zasoby muszą być wykorzystywane w racjonalny sposób. Ścieki, jako zanieczyszczona, chorobotwórcza i niezdatna do użycia woda stanowią dla człowieka duży problem. Oczyszczanie ich za pomocą metod mechanicznych, fizyczno – chemicznych i biologicznych stanowi rozwiązanie problemu. W miejscach gdzie brak zbiorczych sieci kanalizacyjnych najczęściej stosuje się szamba lub przydomowe oczyszczalnie ścieków. Głównym celem pracy jest zaprojektowanie przydomowej oczyszczalni ścieków dla domu jednorodzinnego. Wykazano, że praca takiej instalacji jest efektywnie i ekologicznie uzasadniona.
Analysis of working and profitability of Septic drain fields
Keywords: woda; oczyszczalnie ścieków; osadnik gnilny; drenaż; filtracja; water; sewage treatment; septic tank; drain; filtering